2019
DOI: 10.1002/tox.22724
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of ochratoxin A‐induced oxidative stress‐mediated apoptotic processes and impairment of embryonic development in mouse blastocysts by liquiritigenin

Abstract: Ochratoxin A (OTA), a mycotoxin constituent of a range of food commodities, including coffee, wine, beer, grains, and spices, exerts toxicological and pathological effects in vivo, such as nephrotoxicity, hepatotoxicity, and immunotoxicity. In a previous report, we highlighted the potential of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 62 publications
1
2
1
2
Order By: Relevance
“…The data indicated that exposure to OTA through feed leads to apoptosis, similar to observations made in other studies [46,47]. Some other studies have reported that OTA-contaminated diets had a significant effect on LDH levels, Caspase3 activities, AKT levels, and numbers of apoptotic nuclei [48,49]. Here, it was demonstrated that mRNA expressions of Bax, P53, and Caspase3 were increased in the OTA-exposed kidneys, while levels of PI3K, AKT, and Bcl-2 decreased.…”
Section: Oxidative Medicine and Cellular Longevitysupporting
confidence: 88%
“…The data indicated that exposure to OTA through feed leads to apoptosis, similar to observations made in other studies [46,47]. Some other studies have reported that OTA-contaminated diets had a significant effect on LDH levels, Caspase3 activities, AKT levels, and numbers of apoptotic nuclei [48,49]. Here, it was demonstrated that mRNA expressions of Bax, P53, and Caspase3 were increased in the OTA-exposed kidneys, while levels of PI3K, AKT, and Bcl-2 decreased.…”
Section: Oxidative Medicine and Cellular Longevitysupporting
confidence: 88%
“…At both micro and nanomolar concentrations, OTA boosted blastocyst mitochondrial function and reduced mitochondria/ROS colocalization. Mouse blastocysts, exposed in vitro for 24 h to OTA during the morula/blastocyst transition exhibited loss of mitochondria membrane potential and increased ROS generation (Hsuuw et al 2013;Huang et al 2019). A possible explanation of discrepancies with our study could be the exposure phase.…”
Section: Discussioncontrasting
confidence: 83%
“…Bax and Bcl-2 are two important proteins that respond to mitochondrial apoptosis; Bax is a proapoptotic protein, and Bcl-2 is an antiapoptotic protein [38,43]. In addition, myocardial injury in rats causes apoptosis by activating the caspase family [44][45][46]. This study detected cardiomyocyte apoptosis by TUNEL assay…”
Section: Discussionmentioning
confidence: 92%